Structural Analysis of an Avr4 Effector Ortholog Offers Insight into Chitin Binding and Recognition by the Cf-4 Receptor. Issue 8 (8th July 2016) - Kohler, Amanda C.; Chen, Li-Hung; Hurlburt, Nicholas; Salvucci, Anthony; Schwessinger, Benjamin; Fisher, Andrew J.; Stergiopoulos, Ioannis
Abstract : Structure-function analysis reveals that chitin binding by Pf-Avr4, a fungal Avr4 effector, is largely separable from recognition by the cognate Cf-4 receptor. Abstract: Chitin is a key component of fungal cell walls and a potent inducer of innate immune responses. Consequently, fungi may secrete chitin-binding lectins, such as the Cf-Avr4 effector protein from the tomato pathogen Cladosporium fulvum, to shield chitin from host-derived chitinases during infection. Homologs of Cf-Avr4 are found throughout Dothideomycetes, and despite their modest primary sequence identity, many are perceived by the cognate tomato immune receptor Cf-4. Here, we determined the x-ray crystal structure of Pf-Avr4 from the tomato pathogen Pseudocercospora fuligena, thus providing a three-dimensional model of an Avr4 effector protein. In addition, we explored structural, biochemical, and functional aspects of Pf-Avr4 and Cf-Avr4 to further define the biology of core effector proteins and outline a conceptual framework for their pleiotropic recognition by single immune receptors. We show that Cf-Avr4 and Pf-Avr4 share functional specificity in binding (GlcNAc)6 and in providing protection against plant- and microbial-derived chitinases, suggesting a broader role beyond deregulation of host immunity. Furthermore, structure-guided site-directed mutagenesis indicated that residues in Pf-Avr4 important for binding chitin do not directly influence recognition by Cf-4 and further suggested that the property of recognition is structurally separated or does not fully overlap with the virulence function of the effector.